2018
DOI: 10.1590/1806-90882017000500008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Structure of Macaw Palm: Implications for Genetic Variability Sampling

Abstract: The macaw palm, Acrocomia aculeata (Jacq.) Lodd. ex Mart., is a Brazilian native species with great potential for biofuel production. The aim of this work was to analyze macaw palm genetic diversity to structure and assist in the definition of sampling strategies for germplasm banks. Forty-six microsatellite markers, from which seven polymorphic markers were used to evaluate 103 macaw palm individuals collected from different Brazilian locations. The polymorphic markers were used to generate a dissimilarity ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In Acrocomia, microsatellites or simple sequence repeats (SSR) have been the most used molecular markers, with the main objective of evaluating the genetic diversity and structure of natural populations and germplasm banks [18,19,[36][37][38]. Other approaches include the use of internal transcribed ribosomal 18S-26S spacer (ITS region) [39] and random amplification of polymorphic DNA (RAPD) markers [40]. However, most studies have focused on A. aculeata [18,20,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In Acrocomia, microsatellites or simple sequence repeats (SSR) have been the most used molecular markers, with the main objective of evaluating the genetic diversity and structure of natural populations and germplasm banks [18,19,[36][37][38]. Other approaches include the use of internal transcribed ribosomal 18S-26S spacer (ITS region) [39] and random amplification of polymorphic DNA (RAPD) markers [40]. However, most studies have focused on A. aculeata [18,20,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Lanes et al (2015) analyzed the genetic diversity of individuals from Acrocomia from different Brazilian localities with microsatellite markers and identified the formation of two main groups, one formed by individuals from the Pantanal region of Mato Grosso do Sul with high genetic differentiation according to the F ST index. Similarly, the information generated by the ITS region of 67 A. aculeatagenotypes from the study by Silva et al (2017) identified the formation of four haplotypes, two of them shared by genotypes of São Paulo and Minas Gerais, and a unique haplotype of genotypes collected in Mato Grosso do Sul near the Paraguay border, also suggesting the occurrence of different species of Acrocomia. Some phenotypic characteristics have been used to distinguish species from the genus Acrocomia (Lorenzi 2010).…”
Section: Delimitation Of Species a Aculeata And A Totaimentioning
confidence: 76%
“…Lanes et al (23) used microsatellite markers to demonstrate the marked genetic differences of A. aculeata between individuals from the Pantanal region, State of Mato Grosso do Sul, Brazil, and other regions of the country. Similarly, Silva et al (27) analyzed the variation in the internal transcribed spacer (ITS) region and identified four haplotypes. Two were shared by genotypes from São Paulo and Minas Gerais, and one was exclusive to genotypes collected in Mato Grosso do Sul.…”
Section: A Aculeatamentioning
confidence: 99%
“…Two were shared by genotypes from São Paulo and Minas Gerais, and one was exclusive to genotypes collected in Mato Grosso do Sul. The morphological characteristics of A. aculeata include larger fruits (3.5 and 5.0 cm) and a pulp oil content that can reach approximately 78% (27,(68)(69)(70) while the fruits of A. totai are smaller (2.5 and 3.5 cm) with a pulp oil content between 26% and 33% (68, 71, 72. In Brazil, A. totai is considered to be restricted to the State of Mato Grosso do Sul [4,69,70]. An interesting finding of our study was that samples from Xambrê, Paraná (XAM) and a sample from Palmas, Tocantins (PAL_182), considered as A. aculeata based on Lorenzi et al, [4] taxonomic classification, were attributed to cluster 2 of A. totai by the Bayesian analysis (Fig 2), by been proven, our results are consistent with the information reported on the Flora do Brazil 2020 website [15], indicating the possible occurrence of A. totai in these states.…”
Section: A Aculeatamentioning
confidence: 99%
See 1 more Smart Citation